Inovasi Pencegahan Hipertensi dengan Penggunaan Akupresur dan Minuman Bahan Herbal Sederhana - Komang Rosa Tri Anggaraeni; Ida Ayu Suptika Strisanti (JURNAL KESEHATAN PRIMER, 2026)
Background: Hypertension remains a major health problem contributing to morbidity and mortality, including in Indonesia. Effective, safe, and easy-to-implement preventive strategies are needed. Acupressure and natural herbal ingredients such as celery, cucumber, and pineapple are known to lowering the blood pressure by doing vascular relaxation, diuretic effect, regulation of the autonomic nervous system. Objectives: To determine the effectiveness of a pairing of acupressure and consumption of a simple herbal drink (celery, cucumber, and pineapple) in reducing blood pressure among individuals at risk of hypertension. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The research used 60 participants aged 40–65 years with prehypertensive blood pressure levels. The intervention was conducted over four weeks, consisting of self-administered acupressure twice daily at points LI11 (Quchi), GB20 (Fengchi), and LI4 (Hegu), along with daily consumption of 200–250 ml of herbal juice. Data were analyzed using a paired t-test with a significance level of p < 0.05. Results: The average respondent’s systolic blood pressure decreased from 132.40 mmHg before the intervention to 127.80 mmHg after the intervention, while diastolic blood pressure decreased from 79.28 mmHg to 76.78 mmHg. Statistical analysis showed a crucial reduction in both systolic and diastolic blood pressure (p = 0.000). Conclusions: The combination of acupressure and simple herbal beverage effectively lowers blood pressure in individuals at risk of hypertension. This approach is safe, affordable, and can be independently applied in the community as a non-pharmacological preventive strategy against hypertension.